LIVRO INFANTIL MULTIFORMATO EM SISTEMA PICTOGRÁFICO:: LANÇANDO A SEMENTE DA INCLUSÃO PELA VIA LITERÁRIA - Lago, Mara Rita Araújo (2025)
In this study resulting from the Master's dissertation defended in 2023, the relevance of multiformat children's books for the stimulation of storytelling for students with autism was highlighted. The objective of this study was to describe the interaction between the children and the multiformat children's book, based on the observations made explicit by the teachers in the research questionnaire. The main methodological technique was based on a qualitative approach, data collection took place through bibliographic, documentary, online and face-to-face research, in an early childhood education school in the Municipality of Castanhal (PA), with the application of a workshop, having as subjects teachers and their students with ASD (Autism Spectrum Disorder). Our analysis reveals that the material applied to the students by the teachers was able to stimulate the students' curiosity and interaction.